Tanshinone IIA promotes vascular normalization and boosts Sorafenib’s anti-hepatoma activity via modulating the PI3K-AKT pathway - Qin, Chengdong; Liu, Siyuan; Zhou, Shiqi; Xia, Xianghou; Hu, Jiejie; Yu, Yang; Ma, Dening (Frontiers in Pharmacology, 2023)
Angiogenesis is an essential feature of liver cancer. Tumor hypoxia results from abnormal vessel architecture. Numerous studies have sufficiently demonstrated that Tanshinone IIA (Tan IIA) can increase blood flow and enhance microcirculation. The objectives of this study are to: 1 assess the impact of Tan IIA on tumor angiogenesis and architecture, 2 determine the impact of Tan IIA on tumor hypoxia and susceptibility to Sorafenib, and 3 clarify the relevant mechanisms. CCK8 and flow cytometry measured cell proliferation and apoptosis, respectively. Tube creation assay was used to investigate medication effects on angiogenesis and structure. Drug effects on tumor development, metastasis, and hypoxic tumor microenvironment are assessed in an orthotopic xenograft model of liver tumors. Protein expression was measured by Western blotting and immunohistochemistry. Our results demonstrated that Tan IIA could not reduce tumor proliferation or enhance Sorafenib's anti-tumor effect in vitro. Nevertheless, it can prevent Sorafenib from demolishing the typical vascular structure and aid sorafenib in blocking the recruitment of vascular endothelial cells by liver cancer cells. Although Tan IIA cannot inhibit tumor growth in vivo, it can significantly boost Sorafenib's inhibitory effect on liver cancer, alleviate tumor microenvironment hypoxia, and minimize lung metastasis. This effect may be achieved by reducing HIF-1α and HIF-2α expression via the PI3K-AKT signal pathway. Our results reveal the mechanism of Tan IIA in normalizing tumor blood vessels, provide innovative concepts and approaches to overcome chemotherapy resistance, and provide a theoretical basis for the clinical transformation and usage of Tan IIA.